2014
DOI: 10.1179/1749631414y.0000000032
|View full text |Cite|
|
Sign up to set email alerts
|

AEA 2012 Conference Reading: Socioecological dynamics at the time of Neolithic transition in Iberia

Abstract: In the above paper the title should have read as 'Socioecological dynamics at the time of Neolithic transition in Iberia'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…This also extends earlier approaches by several scholars (Cruz Berrocal 2012;Martins et al 2015;Bernabeu Aubán et al 2014;Balsera et al 2015aBalsera et al , 2015b. The results of Isern et al (2014) indicated a general east-northwest trending gradient and a multi-source introduction pattern for the earliest agriculture, advancing from the northeast and southeast in Mediterranean Iberia with further probable southern routes, likely related to north Africa (Gibaja and Carvalho 2010;Rojo et al 2010;Cortés et al 2012;Linstädter et al 2012;Manning and Timpson 2014;Zilhão 2014).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…This also extends earlier approaches by several scholars (Cruz Berrocal 2012;Martins et al 2015;Bernabeu Aubán et al 2014;Balsera et al 2015aBalsera et al , 2015b. The results of Isern et al (2014) indicated a general east-northwest trending gradient and a multi-source introduction pattern for the earliest agriculture, advancing from the northeast and southeast in Mediterranean Iberia with further probable southern routes, likely related to north Africa (Gibaja and Carvalho 2010;Rojo et al 2010;Cortés et al 2012;Linstädter et al 2012;Manning and Timpson 2014;Zilhão 2014).…”
Section: Introductionsupporting
confidence: 66%
“…) for the entire Peninsula deploying geographic information systems (GIS) and (b) the growing number of high-quality radiocarbon assays available for the early Neolithic in Iberia. Drawing on these developments, recent contributions to the Neolithic transition in Iberia have provided fresh insights into its expansion dynamics based on computational modeling and the sophisticated manipulation of calibrated radiocarbon estimates (Zilhão 2011;Cruz Berrocal 2012;Isern et al 2014;Balsera et al 2015aBalsera et al , 2015bBernabeu Aubán et al 2014, 2015Fano et al 2015;García-Martínez de Lagrán 2015;Pardo Gordó et al 2015;Martins et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the archaeological record for the Late Mesolithic in many areas of the West Mediterranean is still quite modest, there are Late Mesolithic sites on the coast of Portugal that provide good evidence of the side-by-side coexistence of late hunter-gatherers and first farmers over a fair arc of time (8). On the other hand, there is still a shortage of good evidence for the nature and temporal length of Mesolithic and Neolithic coexistence along the Spanish coast (37). On the Mediterranean coasts of France and northern Italy, the evidence so far does not support the idea of coexistence of any real length of time (38,39).…”
Section: Resultsmentioning
confidence: 98%
“…So far, all of the Late Mesolithic sites found in Iberia are located either near the coast or else on a river valley (e.g., the Ebro Valley), with no evidence for Mesolithic populations in the central Meseta (37). In this light, and with the aim of evaluating the effects of interaction, we consider that Mesolithic populations were restricted to coastal cells.…”
Section: Resultsmentioning
confidence: 99%
“…In these experiments, we model the effects of increasing population, reducing fallowing intervals, and resource management strategies on barranco incision (Table 1). We situate these experiments in the real-world landscape of the Penaguila Valley in northern Alicante Province, Spain, which is the location of one of the earliest farming settlements (i.e., Neolithic) in the region [27,28]. Today, the valley is dissected by deeply entrenched barrancos containing incised sections that appear to postdate early Neolithic occupation of the valley.…”
Section: Introductionmentioning
confidence: 99%